Managing Global Supply Chains: Contemporary Global Challenges in Supply Chain Management - Basu, Ron (Routledge, 2024)
This new edition specifically focuses on seven contemporary challenges that have affected global supply chain management. Recent disruptions to global supply chains created by COVID-19 and the Ukraine conflict have resulted in significant geographical shifts in supply and demand. High inflation and the cost of living crisis have, in turn, created problems for finely-tuned global supply chains.